Habitat selection by adult Golden Eagles Aquila chrysaetos during the breeding season and implications for wind farm establishment. Issue 2 (2nd April 2016) - Singh, Navinder J.; Moss, Edward; Hipkiss, Tim; Ecke, Frauke; Dettki, Holger; Sandström, Per; Bloom, Peter; Kidd, Jeff; Thomas, Scott; Hörnfeldt, Birger
ABSTRACT: Capsule: Global Positioning System (GPS)-tagged adult Golden Eagles Aquila chrysaetos breeding in forests in northern Sweden selected clear-cuts, coniferous forests with lichens and steep slopes during the breeding season but avoided wetlands and mixed forest. Aims: To investigate the habitat selection patterns of tree-nesting Golden Eagles, and identify how potential conflicts with wind farm development could be minimized. Methods: The study is based on GPS tracking data from 22 adult eagles. We estimated home range sizes using a biased random bridge approach and habitat selection patterns using resource selection functions following a use-availability design. Results: Core home range size among adults was variable during the breeding season (5–30 km 2 ). Individual movement extents were variable, but sexes did not significantly differ in their scale of movement. At the landscape scale, individuals selected for clear-cuts and coniferous forest with ground lichens, whereas wetland, water bodies and mixed forest were avoided. Steeper and south facing slopes were selected for, whereas, north facing slopes were avoided. Conclusions: Potential conflicts between eagles and wind energy establishment can be reduced if wind farms are placed away from steep slopes, minimizing areas that are clear-cut during construction, and locating turbines within dense, young and other less favoured forest habitats.